Exploring the Use of Mobile Assisted Language Learning in University Students Context - Alvons Habibie (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2021)
One of the technological tools that has experienced significant developments in this era is the smartphone. The use of smartphones among millennials, especially students, is inevitable. Therefore, this study aims to see students' perceptions on using MALL (Mobile Assisted Language Learning) in the English learning process at IAIN Sultan Amai Gorontalo. The method used was a qualitative design by surveying 55 students majoring in English Education. Of the 55 students, only 50 responded to the questionnaire given. This questionnaire contained questions about students’ demographic information as well as students’ perceptions about the use of MALL by using five scales, namely Strongly Agree, Agree, Neutral, Disagree, and Strongly Disagree. The results showed that the respondents consisted of 40 women and ten men. The age of the respondents is between 20-24. All respondents have smartphones, 4 of them have tablets and 46 have laptops. From the results of the survey above, it can be said that students stated that smartphones are very helpful tools for their daily activities. The use of gadgets in the learning process, especially language learning, deserves to be elaborated with other learning methods or media. In the era of technological sophistication, the presence of smartphones requires teachers to be more creative in using various applications and content attached to this gadget. Current students cannot be separated from smartphones. The result of this study shows how smartphones are tools that enable better language competency in students, but of course, with proper and wise supervision and use.